SOME PROBLEMS OF LEGAL REGULATION OF COPYRIGHT AND COPYRIGHT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines current copyright practices and how well they comply with court decisions. In addition, the article describes the changes made by the author to copyright laws and their reasons in accordance with international norms.